A identificação na melancolia: do objeto perdido ao objeto a - Barreto, Clarissa Maia Esmeraldo (2016)
Melancholia is a psychological disorder characterized by deep and terrible suffering and pain. Its studies still evokes questions among psychoanalytical society, particularly as regards its categorization as neurosis or psychosis. In this work, the authors started with the difficulty found through literature review, both in Freud and in today's authors, in specify the object concerning of the identification in this affection. Thinking about the nature of this linked chain is important to understand more specific clinical aspects with subjects suffering with this structure. In this context, this research intended to contribute to the clarification of the identification process to what Freud called as lost object in melancholia – which gives a peculiar coloring to this condition – and shed a light on current debates surrounding this clinic. Consequently, the methodological approach was focused in two paths: the study of the concept of identification and the development of the object term by Freud and its rereading established by Lacan. From this, the authors analyzed what is particular of melancholia, illustrating these findings through clinical case of Louis Althusser, final part of this paper. One detail shone through the research results, namely: that the target of the melancholic identification, to which Freud had named the lost object, it is not the object as cause of desire, but the object in its real face, as proposed by Lacan in his seminar on anxiety. This process is controlled by primary identification to the father of personal prehistory, not symbolized by the identification to the unary trait – that is, by the incidence of the Name of the Father – a model that is observed especially in psychosis. This factor explains various clinical aspects of this structure, as the submission to the empire oh the Thing by the action of the death instinct, the constitution of the self and suicide.